The Analysis of Environmental Performance to Moderate The Effect of Financial Performance on Firm Value - Eti Yustika Hartono; Hadi Pramono; Edi Joko Setyadi; Annisa Ilma Hartikasari (Journal of Finance and Business Digital, 2023)
This study aims to determine how the impact of the implementation of Financial Performance on Firm Value with Evironmental Performance as a moderating variable. The population of this study is all companies listed on Bursa Efek Indonesia in 2019-2021. The sample has been determined by purposive sampling technique, the predetermined criteria was successful obtained 63 of sample companies listed on Bursa Efek Indonesia and obtained a PROPER rating. Data were analyzed using Moderating Regression Analysis. The result of this research indicated that : 1) ROA has a negative effect on firm value, 2) ROE has a positive effect on firm value, 3) Environmental performance is able to moderate ROA on firm value, 4) Environmental Performance unable to moderate ROE on firm value.